Genetic counselors' (GC) knowledge, awareness, understanding of clinical next‐generation sequencing (NGS) genomic testing. (22nd January 2015) - Boland, P.M.; Ruth, K.; Matro, J.M.; Rainey, K.L.; Fang, C.Y.; Wong, Y.N.; Daly, M.B.; Hall, M.J.
Abstract : Genomic tests are increasingly complex, less expensive, and more widely available with the advent of next‐generation sequencing (NGS). We assessed knowledge and perceptions among genetic counselors pertaining to NGS genomic testing via an online survey. Associations between selected characteristics and perceptions were examined. Recent education on NGS testing was common, but practical experience limited. Perceived understanding of clinical NGS was modest, specifically concerning tumor testing. Greater perceived understanding of clinical NGS testing correlated with more time spent in cancer‐related counseling, exposure to NGS testing, and NGS‐focused education. Substantial disagreement about the role of counseling for tumor‐based testing was seen. Finally, a majority of counselors agreed with the need for more education about clinical NGS testing, supporting this approach to optimizing implementation.